Peningkatan Hasil Belajar Siswa Kelas VIII Melalui Penerapan Strategi Everyone Is A Teacher Here Pada Pembelajaran Sejarah Kebudayaan Islam: Penelitian - Bintang Arif Samudra; Muhammad Nasrullah Ramadhana; Burhanuddin; Nurmawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This Classroom Action Research (CAR) aimed to improve and enhance the learning process and outcomes of students in Islamic Cultural History (SKI) subject, specifically on the topic of the Prophet's Da'wah Strategy in Mecca, through the implementation of the Everyone Is A Teacher Here learning strategy. This strategy was essential for fostering students' courage, activity, and learning responsibility. The study employed a quantitative approach with a Classroom Action Research (CAR) design, conducted in two cycles. The subjects were 17 students of class VIII-A at SMP Muhammadiyah 56 Binjai Timur. Data collection techniques included observation to measure activity, learning outcome tests, and interviews. The analysis results indicated a significant increase in learning outcomes after the implementation of the Everyone Is A Teacher Here strategy. Before the intervention, the students' average scores were below the Minimum Completeness Criteria (KKM). Based on the analysis of activity data, there was a drastic increase in student activity from pre-cycle 68 to 82 in Cycle I, and reaching 87 in Cycle II. Quantitatively, the average learning outcome score in Cycle I was 5.6 with a classical completeness percentage of 28% , and in Cycle II, the average score increased rapidly to 7.9 with a classical completeness percentage reaching 82%. Qualitatively, in Cycle II, students' questions began to develop and demonstrated articulated ideas, and students' interest and motivation to learn increased. Therefore, it was concluded that the Everyone Is A Teacher Here strategy was effective in improving SKI learning outcomes, and classical completeness reached the target set in Cycle II.